A impossibilidade da experiência humana nas determinações sociais contemporâneas - Binja, Elias Justino Bartolomeu (2014)
Founded on the theme The Impossibility of Human Experience in Contemporary Social Determinations , this study aims at analyzing the relationship between Multiculturalism and Ideology, focusing the issue of the concept of Recognition in Charles Taylor s theory about identity formation. While exploring the concept of ideology, our intention is to analyze and evaluate its ontological usage in interpersonal relations in the dynamics of multicultural practice. This research aims therefore to grasp and clarify the impossibility of interpersonal experiences, the latter being understood as intersubjective acquaintanceship either inside different groups of a same society or in intercultural relations among societies with different traditions. On the other hand, it is not our intention that this research be limited to a frame of skepticism regarding social and cultural life of contemporary societies. Thus, this is the reason why our study has as its final purpose the development of concepts which may lead to the building up of a valorative vocabulary that allows us to overcome this hypothetical impossibility of genuine social acquaintanceship and intimacy. Our theoretical background is related to the investigation of such possible forms of social partnership and intimacy, forms which have been created by multiculturalism and which give way to a kind of opening space that might clarify the type of speech produced in our times. We also search to provide a conceptual basis that allows us to create new modes of being intersubjective human beings.